Analisis Produktivitas Mesin Section Forging Press Menggunakan Metode Overall Equipment Effectiveness (OEE) Di PT. Fujita Indonesia - Dinda Febri Lestari; Wahyudin Wahyudin (Peneliti.net, 2022)
Automotive component manufacturers often use machinery in their production process. Machines that are often used will usually experience problems that cause hampered production processes that affect the productivity of the machine. This study aims to analyze the productivity levels of Section Forging Press machines 2, 3 and 4 in PT. Fujita Indonesia. The method used in this study is the Overall Equipment Effectiveness (OEE) method. From the results of research using the Overall Equipment Effectiveness (OEE) method it is known that the average productivity of Section Forging Press machines 2 is 54%, Section Forging Press 3 is 63% and Section Forging Press 4 is 60%. The average productivity of Section Forging Presses 2, 3 and 4 is 59% which still does not meet the standards of the Japan Institute of Plant Maintenance (JIPM) where the OEE provisions are 85%. The productivity levels of Section Forging Press Machines 2, 3 and 4 can be said to have not produced well.